The Effect of Constructive Islamic Games on Improving Communication Skills of Preschoolers - Anita Yuliani; Nike Artha Puspitasari; Salsabila Faturachmah (Oksitosin : Jurnal Ilmiah Kebidanan, 2025)
Preschool is a critical period for children's development, where they begin to cultivate essential communication skills. This study aims to explore the impact of Constructive Islamic Games on improving communication skills among preschoolers. Utilizing a pre-experimental design with a one-group pre-test and post-test methodology, the sample consisted of 45 children aged 2 to 6 years with developmental delays. Data were collected through observations and analyzed using the Wilcoxon test. The results indicated that the implementation Constructive Islamic Games significantly enhanced children's communication skills, with an increase from 45.3% of children categorized as "Poor" to 73.3% categorized as "Good" following the intervention. These findings underscore the importance of Constructive Islamic Games methods in early childhood education.